TAKHARUJ ADALAH PENDEKATAN DALAM MEMBAGI HARTA WARISAN SECARA ADIL - Mardani Mardani (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
This article discusses the division of inheritance based on the concept of takharuj. Takharuj is a legal term that refers to the freedom of heirs to reject the portion of inheritance they should receive. This article explains the concept of takharuj in the context of inheritance law, including its background, objectives, and application. Inheritance division is a complex and sensitive process, and the concept of takharuj provides an alternative for heirs who may have strong reasons to refuse the inheritance. Reasons such as high debts, family disputes, or financial considerations can be factors in the heirs' decision to reject the inheritance. The article also describes some issues that may arise in the implementation of the concept of takharuj, including its impact on fair inheritance distribution and inheritance tax obligations. Various legal systems have different approaches in applying the concept of takharuj, and the article provides a general overview of these differences. Justice and the public interest should be the foundation for regulating and implementing the concept of takharuj in inheritance division. In conclusion, this article emphasizes the complexity and importance of the concept of takharuj in inheritance division. This concept provides flexibility for heirs to make decisions that align with their needs and interests. However, the implementation of the concept of takharuj should be done carefully and in accordance with the principles of justice, to ensure fair inheritance distribution and safeguard the interests of all parties involved. Keywords: Inheritance division, concept of takharuj, justice.